2021
DOI: 10.31234/osf.io/2teu5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotional experiences in technology-mediated and in-person interactions: An experience-sampling study

Abstract: As the ubiquity of digitally mediated communication grows, so does the number of questions about the costs and benefits of replacing in-person interactions with digital ones. In the present study, we used a daily diary design to examine how people’s emotional experiences vary across in-person, video-, phone-, and text-mediated interactions in day-to-day life. We hypothesized that individuals would report less positive affect and more negative affect after less life-like interactions (where in-person is defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Three main practical implications can be derived from the results of this study: 1) Organizations should rely on synchronous, audio-visual work tools (instead of asynchronous text-based tools) to the extent possible ( Petrova & Schulz, 2021 ). 2) Organizations should make sure that all tools are easy to use and standardize on a limited number of tools (if possible).…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…Three main practical implications can be derived from the results of this study: 1) Organizations should rely on synchronous, audio-visual work tools (instead of asynchronous text-based tools) to the extent possible ( Petrova & Schulz, 2021 ). 2) Organizations should make sure that all tools are easy to use and standardize on a limited number of tools (if possible).…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…In addition, regular communication technologies such as the telephone and video conferencing may not provide a 'feeling of presence', due to the absence of touch and the inability to make real eye contact (Cohen et al, 2017). Recent technological advances by Cohen et al showed that 3D virtual reality and haptic technology can be used to recreate a feeling of presence, which might be expected to increase the positive emotional impact of such contact (Petrova & Schulz, 2021). Making such technologies available for the wider population would be a valuable direction for innovation and research.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Nevertheless, it should be noted that the buffering effect of a preference for shared coping was only evident when partners had in-person contact. This finding may be explained by the importance of in-person contact for fostering feelings of support (Petrova & Schulz, 2021). Moreover, the time of data collection (i.e., societal lockdown) may partially account for the moderating effect of in-person contact.…”
Section: Discussionmentioning
confidence: 99%